CryoSat-2 interferometric mode calibration and validation: A case study from the Austfonna ice cap, Svalbard - Morris, Richard Ashley; Moholdt, Geir; Gray, Laurence; Schuler, Thomas; Eiken, Trond (Remote Sensing of Environment, 2022)
Satellite radar altimetry is widely used to measure glacier and ice sheet elevation changes, but can suffer from uncertainties related to geolocation and signal penetration. The unique capabilities of ESA's CryoSat-2 allow for accurate geolocation but impacts from signal penetration persist. This study uses surface elevations from Global Navigation Satellite System and airborne laser transects over the Austfonna ice cap, Svalbard, to measure the elevation bias of CryoSat-2 Point-of-closest-approach (POCA) and swath points, and to provide validation for estimates derived through the application of a least-squares plane-fit algorithm to these data. The mean elevation bias of swath points varies between 1 and 1.5 m of penetration, which is close to observed winter snow depths. Histograms of POCA elevation bias for the applied leading-edge retracker peak near the surface, with a distribution skewed towards the sub-surface. At the onset of surface melt, surface scattering dominates backscatter, and penetration reduces. This results in spurious peaks in derived elevation and mass change time series. In spite of this seasonal variability in elevation bias, the validation dataset demonstrates that the CryoSat-2 estimates are robust on multi-year timescales. The transition from volume to surface scattering suggests the potential to estimate yearly snowpack thickness.